Kualitas pelayanan di Sekolah Tinggi XYZ masih belum sesuai dengan apa yang diharapkan, misalnya masih terjadi antrean pendaftaran, pembayaran, lamanya pelayanan akademik, daya tampung parkir, ruang kuliah, akses perpustakaan, keamanan, dan lain-lain. Pada penelitian ini bertujuan untuk mengetahui kualitas pelayanan Sekolah Tinggi XYZ terhadap kepuasan mahasiswa. Adapun metode yang digunakan pada penelitian ini adalah metode integrasi Servqual, Kano dan Quality Function Deployment (QFD), dengan - Teguh Aprianto; Abdul Fatah (Jurnal Rekayasa Sistem Industri, 2021)
The service quality at XYZ High School is still not in accordance as expected. There are still queues for registration, payments, length of academic service, parking capacity, lecture room, library access, security, and etc. This study is conducted to find out the service quality of XYZ high school towards the students' satisfaction. The methods used in this research are the integration method of Servqual, Kano and Quality Function Deployment (QFD), using 5 Servqual dimensions, those are Tangible, Reliability, Responsiveness, Assurance, and Empathy. The gap value of all service attributes provided is negative. It means that the service performance still can't fulfill the students' expectation. Based on the integration calculation of the Servqual, Kano and QFD methods, there are 16 of 31 service attributes need to be improved. The easy attribute in accessing information by online can become priority with the important level of 23.17 by constructing an online integrated information to become the priority technical response which is conducted for the improvement with the percentage of 21.04%.